Sociocultural and health system factors associated with mortality among febrile inpatients in Tanzania: a prospective social biopsy cohort study - Snavely, Michael E (BMJ Glob Health, 2018)
INTRODUCTION: Communicable diseases are the leading causes of death in Tanzania despite the existence of effective treatment tools. We aimed to assess the sociocultural and health system factors associated with mortality from febrile illness in northern Tanzania. METHODS: We interviewed febrile inpatients to determine prevalence of barriers in seeking or receiving care and grouped these barriers using the Three Delays model (delays at home, in transport and at healthcare facilities). We assessed 6-week mortality and, after matching on age, gender and severity of illness, measured the association between delays and mortality using conditional logistic regression. RESULTS: We enrolled 475 children, of whom 18 (3.8%) died, and 260 adults, of whom 34 (13.0%) died. For children, home delays were not associated with mortality. Among adults, a delay in care-seeking due to not recognising severe symptoms was associated with mortality (OR: 3.01; 95% CI 1.24 to 7.32). For transport delays, taking >1 hour to reach a facility increased odds of death in children (OR: 3.27; 95% CI 1.11 to 9.66) and adults (OR: 3.03; 95% CI 1.32 to 6.99). For health system delays, each additional facility visited was associated with mortality for children (OR: 1.59; 95% CI 1.06 to 2.38) and adults (OR: 2.00; 95% CI 1.17 to 3.41), as was spending >4 days between the first facility visit and reaching tertiary care (OR: 4.39; 95% CI 1.49 to 12.93). CONCLUSION: Our findings suggest that delays at home, in transport and in accessing tertiary care are risk factors for mortality from febrile illness in northern Tanzania. Interventions that may reduce mortality include community education regarding severe symptoms, expanding transportation infrastructure and streamlining referrals to tertiary care for the sickest patients.